2023
DOI: 10.3389/fphys.2022.1078301
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in stretch-induced hypertrophy, maximal strength and flexibility gains

Abstract: Introduction: If the aim is to increase maximal strength (MSt) and muscle mass, resistance training (RT) is primarily used to achieve these outcomes. However, research indicates that long-duration stretching sessions of up to 2 h per day can also provide sufficient stimuli to induce muscle growth. In RT literature, sex-related differences in adaptations are widely discussed, however, there is a lack of evidence addressing the sex-related effects on MSt and muscle thickness (MTh) of longer duration stretch trai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 84 publications
0
8
0
Order By: Relevance
“…The involvement of key neural systems (dopamine, μ opioid receptors, kappa opioid receptors, and brain-derived neurotrophic factor) in addiction and withdrawal differs greatly between male patients and female patients, which could explain the gender differences in clinical symptoms and treatment efficacy during withdrawal ( Becker and Chartoff, 2019 ). Moreover, a recent study has shown that gender differences also exist in exercise-induced hypertrophy and gains in maximal strength and flexibility ( Warneke et al, 2022 ). Taken together, the possibility of gender differences in exercise-induced improvement in withdrawal symptoms should be a significant concern.…”
Section: Discussionmentioning
confidence: 99%
“…The involvement of key neural systems (dopamine, μ opioid receptors, kappa opioid receptors, and brain-derived neurotrophic factor) in addiction and withdrawal differs greatly between male patients and female patients, which could explain the gender differences in clinical symptoms and treatment efficacy during withdrawal ( Becker and Chartoff, 2019 ). Moreover, a recent study has shown that gender differences also exist in exercise-induced hypertrophy and gains in maximal strength and flexibility ( Warneke et al, 2022 ). Taken together, the possibility of gender differences in exercise-induced improvement in withdrawal symptoms should be a significant concern.…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, during our pilot testing, we observed that the vertical shin and neutral ankle angle adopted during the bilateral version of the SIPFT [11,[13][14][15][16][17]20] led to the ball of the foot being placed anterior to the contact point between the bar of the rig and the thighs. This is an issue when using single-axis-only force plates (i.e., those that record vertical forces only, which is typical of commercial-grade force plates), as the point of force application (i.e., the ball of the foot) is in front of the bar-thigh interface, which induces a large anterior-posterior force application that cannot be recorded with single-axis force plates.…”
Section: Discussionmentioning
confidence: 99%
“…Half of surveyed strength and conditioning coaches working in football use force plates to regularly assess the force-generating capabilities of their athletes [10]. Force plates have only been used to assess isometric plantar flexion force in studies published since 2022 [11][12][13][14][15][16][17][18][19][20]. Only one study involved football players and included the seated isometric plantar flexor test (SIPFT) to determine its reliability of quantifying peak force [20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the authors tested the effectiveness of 10 minutes’ daily stretching using a stretching board, and were still able to induce significant increases in muscle strength [ 165 ]. The literature investigating stretch-mediated (≥ 30 min per session) hypertrophy is very scarce and has exclusively tested the plantar flexors [ 163 , 166 , 167 , 169 , 170 ]. More research is necessary to address the optimal dose–response relationship with more muscles and diverse participants.…”
Section: Stretch Training As An Alternative To Resistance Trainingmentioning
confidence: 99%